Modelo de suporte à definição do portfólio de produtos de uma empresa mineradora sensível à variedade de produtos e condições de mercado - Keiner Duarte Alvarenga (2015)
In order to remain competitive in different markets niches a company must identify opportunities to expand its sales. To reach new opportunities companies tend to increase the number of products in production line. As a result this movement may increase sales and market share, but not result in higher profits, due to indirect costs could show up in production line. On the other hand, keeping a simpler portfolio can avoid complexity on the production process and reduce production costs. But to turn it into a successful strategy the company must pay attention on market variables like supply, demand, price forecasting and so on. This work has proposed a portfolio optimization method, which includes a model to support long-term planning, based on mixed integer programming, and market intelligence processes.From this method was possible to show that even in the basic industry product variety can be a successful strategy, especially depending on the product pricing dynamics.